Traumatic vertebral artery dissection mimicking central pontine myelinolysis: A case report - Sharmini, J.; Lim, Kheng Seang; Ramli, N.; Tan, Chong Tin (Asean Neurological Assoc, 2010)
A 27 year-old Chinese man, involved in a motor vehicle accident, presented with rapidly progressive pseudobulbar palsy and spastic tetraplegia. Magnetic resonance imaging (MRI) of the brain showed central pontine T2 hyperintensity with an unaffected outer rim, consistent with central pontine myelinolysis. There was no hyponatraemia before MRI and he was neither an alcoholic nor malnourished. Cerebral angiogram confirmed the diagnosis of right vertebral artery dissection. Vertebral artery dissection should be considered in a case with imaging suggestive of central pontine myelinolysis.